1990
DOI: 10.1021/bi00456a030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interleukin 2-stimulated 65-kilodalton phosphoprotein in human T cells

Abstract: We have characterized the cellular proteins which are rapidly phosphorylated by interleukin 2 (IL 2) in a human IL 2 dependent cell line. When treated with IL 2, the phosphorylation of five proteins, 65, 50, 37, 24, and 21 kDa, was found in IL 2 dependent cell lines by two-dimensional gel electrophoretic analysis. After cell conversion from an IL 2 dependent state to an IL 2 independent state, one of the five phosphoproteins, the 65-kDa protein, became constitutively phosphorylated even without addition of IL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Binding Partner-We found that L-plastin interacts with grancalcin and that Ca 2ϩ regulates the interaction in a negative fashion. L-plastin, like other plastin isoforms and fimbrin, is a mosaic protein containing 2 EF-hands, a calmodulin-binding domain, and two actin-binding domains (37). In resting cells, the Ca 2ϩ -binding sites are unoccupied, and most of Lplastin is involved in the cross-linking of F-actin fibers.…”
Section: Fig 7 Camentioning
confidence: 99%
“…Binding Partner-We found that L-plastin interacts with grancalcin and that Ca 2ϩ regulates the interaction in a negative fashion. L-plastin, like other plastin isoforms and fimbrin, is a mosaic protein containing 2 EF-hands, a calmodulin-binding domain, and two actin-binding domains (37). In resting cells, the Ca 2ϩ -binding sites are unoccupied, and most of Lplastin is involved in the cross-linking of F-actin fibers.…”
Section: Fig 7 Camentioning
confidence: 99%
“…I-Plastin has been shown to bind and bundle F-actin in vitro in a Ca2+-regulated manner (27,28). Its exclusive expression in leukocytes (29) and its phosphorylation in response to leukocyte activators such as interleukins 1 and 2 and phorbol esters (30,31) support the hypothesis that I-plastin has a role in cytoskeletal rearrangements during leukocyte activation.…”
mentioning
confidence: 90%
“…LPL is unique in the fimbrin family because it can become phosphorylated on serine in the headpiece region (19,20), suggesting that phosphorylation may be a specific mechanism of regulating LPL function in leukocytes. A variety of inflammatory mediators that activate ␤2 integrins such as chemokines, formylated bacterial peptides, cytokines, immune complexes, and phorbol 12-myristate 1-acetate (PMA), also induce LPL phosphorylation (19,(21)(22)(23)(24)(25). Despite its close association with activation of adhesion, LPL phosphorylation in PMN does not require ␤2 integrin expression (24), suggesting that its serine phosphorylation may precede ␣M␤2 activation.…”
mentioning
confidence: 99%